2004
DOI: 10.1021/ol048356t
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy To Produce β-Peptides:  Use of Alicyclic β-Lactams

Abstract: On p-methylbenzhydrylamine (MBHA) resin, by means of t-Boc chemistry, several tetrapeptides (H-Ala-ACXC-Ala-Gly-NH(2)) containing cyclic beta-amino acid units were prepared. These units were introduced into the growing peptide chain by using Boc-protected beta-lactams with KCN as catalyst in DMF. The method was applicable for both racemic and enantiomeric beta-lactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Finally, isolation of tetrapeptide 437 was achieved in the conditions shown in Scheme . The HPLC analysis indicated that no epimerization occurred during the synthesis …”
Section: Synthesis Of Amino(hydroxy) Acid Derivativesmentioning
confidence: 99%
“…Finally, isolation of tetrapeptide 437 was achieved in the conditions shown in Scheme . The HPLC analysis indicated that no epimerization occurred during the synthesis …”
Section: Synthesis Of Amino(hydroxy) Acid Derivativesmentioning
confidence: 99%
“…Compound (±)-4, our next selected substrate, was obtained by N-Boc protection of lactam (±)-1. Modification of the reported procedure [28] resulted in an increased product yield of this step. ROM of compound (±)-4 was performed analogously to ring opening of (±)-1.…”
Section: Scheme 1 Cross-metathesis Of Lactam (±)-2 With Fluorinated mentioning
confidence: 99%
“…Academic groups have also shown considerable interest in the conformational changes resulting from incorporation of β‐amino acids into peptides 7–10. In addition, β‐peptides frequently exhibit retarded metabolism and are more resistant to protease enzymes.…”
Section: Introductionmentioning
confidence: 99%